Environmental management of solid wastes in Cayetano Heredia Hospital - Cifuentes, Cecilia (2009)
This paper presents the main results of a thesis to obtain the degree of Geographical Engineer. The hospitals generate thousand of tones of waste per year. This waste has a great complexity because they come from toxic, radioactive and infectious materials apart from common wastes. The quantity of this waste is increasing along with the development of our country and there is a public concern related to the impacts on health of a bad dispose of hospital wastes. The main objective of the thesis is proposing a good management of hospital wastes taking into consideration the source and the final disposal. It focuses on the correct classification of the wastes because this reduces the impact. This environmental management has to accomplish the technical normative of our country and takes international experiences that can be applied to the Cayetano Heredia Hospital in Lima and would improve the present standards.